Рільництво у населення степового Дніпровського Лівобережжя у середині II тис. до н. е. - Гершкович, Я.П.; Герасименко, Н.П. (Археологія і давня історія України, 2021)
У статті розглядається рівень розвитку рільництва у населення сабатинівської культури Північного Причорномор’я пізньої бронзової доби. Нові безсумнівні докази існування місцевого рільництва,
в тому числі у відкритому степу, надають палінологічні дані. За добу пізньої бронзи рослинність
зазнала значної мезофітикації. Значне зволоження
клімату безперечно створювало сприятливі умови
для розвитку давнього рільництва. Польові угіддя
знаходились поруч із поселеннями. In the middle of the IInd millennium BC, the
Sabatynivka Culture spread widely from the Lower
Danube and the Lower Transdnistria to the edges of
the Azov Upland, the Prysyvashia, and the Northwestern
and Eastern Crimea. It occurred under the favorable
environment of that time, particularly under the
increase in climatic humidity, which is clearly reflected
in the pollen data from the cultural layer of the Novokyivka
settlement. Dry (Artemisia-Poaceae) steppe
that existed in the south of Ukraine at the turn of the III
and IInd millennia and at the beginning of the IInd millennium
BC were replaced by grassland, and, later,
by mesophytic (forbs-grasses) steppes. The area of the
Oleshia forests and the proportion of broad-leaved genera
in their composition (including mesophilic Carpinus
betulus), expanded. Such climatic and landscape
conditions might enable the mobile transhumant form
of animal husbandry, together with a swidden form of
agriculture. The existence of fields of cultivated cereals
is indicated by the presence of Cerealia pollen in the
cultural layer of the Novokyivka settlement.
The phenomenon of steppe agriculture came to the
end approximately in the XIIth BC when the climatic
aridity increased. The population of the steppe was
forced to change their way of life, vectors of trade relations
and even their belief system. The Sabatynivka
Culture was replaced by the Belozerka Culture, which
was formed under the significant Danube — Transdnistria
influence. In the steppe of the left bank of the
Dnieper, the possibility for farming has narrowed
considerably, all stationary settlements disappeared,
and instead fortified settlements appeared in the low
reaches of almost all large steppe rivers.
In the historical meaning, the Sabatynivka Culture
shared the fate of the Trypillia Culture, whose population,
having developed farming and animal husbandry,
could not survive the social-economic crisis of the second
half of the 4th millennium BC against the background
of environmental deterioration.